Relation between efficiency and energy cost with coordination in aquatic locomotion - Figueiredo, P.; Toussaint, H. M.; Vilas-Boas, J. P.; Fernandes, R. J. (European Journal of Applied Physiology, 2013)
The aim of this study was to establish the relationships between the intracycle velocity variation (IVV) and Froude efficiency (nT), energy cost (C), and index of coordination (IdC) throughout a 200-m freestyle race. Ten male international level swimmers performed a maximum 200 m front crawl swim. Performance was recorded with four below- and two above-water synchronized cameras. Oxygen consumption was measured continuously during the effort, and blood samples were collected before and after the test. IdC, body center of mass` IVV (x, y and z), and nT were also calculated. For assessing C swimmers performed also 50, 100 and 150 m at the same pace as in the 200-m splits to capture blood lactate samples after each 50-m lap of the 200-m effort. Swimmers attained a stable IVV (x, y, and z), as fatigue development along the 200-m effort induced a decrease in velocity, stroke length, stroke frequency, nT, and an increase of IdC. Direct relationships between C and IdC for the second and fourth lap were found: R = 0.63 and R = 0.69 (P < 0.05), respectively. Computing partial correlation, also IdC and nT in the first lap were significantly correlated (R = -0.63, P < 0.05). IdC and nT showed to be significant for the within-subjects correlation (R = -0.45, P = 0.01), and IdC and C for the between-subjects correlation (R = 0.66, P = 0.04). Patterns of coordination modified during the 200-m event in response to the task constraints, observed by the changes in the other studied parameters, and allowing the IVV stability along the effort.